2011
DOI: 10.1016/j.expneurol.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of recovery from neurodegeneration in conditional transgenic SCA1 mice

Abstract: Reliable and objective markers of neuronal function and pathology that can directly assess the effects of neuroprotective treatments in the brain are urgently needed for clinical trials in neurodegenerative diseases. Here we assessed the sensitivity of high field proton magnetic resonance spectroscopy (1H MRS) to monitor reversal of neurodegeneration by taking advantage of a well characterized conditional mouse model of spinocerebellar ataxia type 1 (SCA1), where the cerebellar pathology and ataxic phenotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
2
38
2
Order By: Relevance
“…Only male mice were studied to obviate the need to control for the phase of estrous cycle in female mice (a requirement difficult to reconcile with scanner time availability) and because gender was not shown to influence neurochemical levels in prior MRS studies (Nagae-Poetscher et al, 2004; Pouwels and Frahm, 1998). In addition, exclusion of female mice from the analysis had not changed the findings in our prior study (Öz et al, 2011b). …”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…Only male mice were studied to obviate the need to control for the phase of estrous cycle in female mice (a requirement difficult to reconcile with scanner time availability) and because gender was not shown to influence neurochemical levels in prior MRS studies (Nagae-Poetscher et al, 2004; Pouwels and Frahm, 1998). In addition, exclusion of female mice from the analysis had not changed the findings in our prior study (Öz et al, 2011b). …”
Section: Methodsmentioning
confidence: 80%
“…All tTA mice were also treated with doxycycline from 12 to 24 weeks to account for potential effects of the doxycycline treatment on the neurochemical profiles. Note that our prior study indicated that doxycycline treatment alone does not significantly alter the neurochemical profile in WT mice (Öz et al, 2011b). All mice were scanned at 9.4 tesla (T) before treatment began at 12 weeks and after treatment ended at 24 weeks.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…4,16 In earlier studies by Orr and colleagues, mutant ataxin-1 was completely eliminated and aggregates resolved quickly with recovery of cerebellar pathology. 4 Our results are similar but contrasting in important ways.…”
Section: Discussionmentioning
confidence: 97%
“…11 These data have been recapitulated in transgenic SCA1 mice 12 and were reversed in a conditional mouse model of SCA1. 16 NAA reduction usually precedes neuronal loss, and is used as a marker of neuronal dysfunction. 24 In this work, NAA levels were modestly reduced in control treated SCA1 mice at 20 weeks of age, a time prior to significant PC loss.…”
Section: Discussionmentioning
confidence: 99%